أهمية الدراسات السابقة في تحليل ومقارنة مناهج العلوم: The importance of previous studies in analyzing and comparing science curricula - mohamed youssef, Marwa amin; Abu Bakar, Kaseh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف هذا العمل البحثي إلى محاولة توضيح الضوابط المنهجية في أهمية الدراسات السابقة بصفة عامة في البحث العلمي الأكاديمي وبصفة خاصة في تحليل مناهج العلوم والمقارنة بين مناهج العلوم في الدول المختلفة حيث أنها تُعتبر المؤشر الرئيسي للباحث ومساعدته في تحديد مساره البحثي فهي مصدر إلهام لا غنى عنه للباحثين. وهي أحد الخطوات الرئيسية التي يجب اتباعها في إعداد خطوات البحث مثال ذلك الاطلاع على الأبحاث السابقة ذات العلاقة المباشرة بموضوع البحث. مما يضيف للباحث والموضوع معًا العديد من الفوائد. وتم تطبيق منهجية الهرمية المقلوبة في طرح الدراسات السابقة التي نفذتها الباحثة في الاطروحه الخاصة بي تحليل منهج العلوم و المقارنة بين مناهج العلوم بين الدول المختلفة من الأبعد لمحور الدراسة إلى الغرب لمحور الدراسة ، إضافة إلى الضوابط المنهجية التي يجب الالتزام بها أثناء عرض الدراسات السابقة ومعايير انتقائها والتي أوضحت الباحثة متمثلة في تنفيذ خريطة مفاهيم توضح هذه الضوابط ،وبذلك يتضح ما يقدمه الباحث من أفكار جديدة تخدم العملية البحثية في تحليل منهج العلوم والدراسات المقارنة لمناهج العلوم في دول مختلفة بناء على معايير مختلفة .من خلال عرض نماذج تطبيقية دراسات سابقة في تحليل ومقارنة مناهج العلوم في دول مختلفة. ABSTRACT This research aims to attempt a clarification of the methodological controls regarding the importance of previous studies in general in academic scientific research, and specifically in the analysis of scientific curricula and the comparison between science curricula in different countries. It is considered the primary indicator for the researcher, aiding them in determining their research path, as it is an indispensable source of inspiration. It is one of the main steps that must be followed in preparing research procedures, such as reviewing previous studies directly related to the research topic. This adds numerous benefits to both the researcher and the subject. The inverted pyramid methodology was applied in presenting the previous studies conducted by the researcher in her thesis, analyzing science curricula and comparing them among different countries from the broader axis of the study to the narrower axis of the study. Additionally, methodological controls that must be adhered to during the presentation of previous studies and the criteria for their selection were elucidated by the researcher, represented in the execution of a conceptual map illustrating these controls. Thus, it becomes clear what new ideas the researcher will present to serve the research process in the analysis of science curricula or studies comparing science curricula in different countries based on different criteria. This is achieved through presenting applied models of previous studies in analyzing and comparing science curricula in different countries.